Unmasking the demand for masks: Analytics of mandating coronavirus masks - Rajeev K. Goel; Shoji Haruna (Metroeconomica, 2021)
This paper analytically examines the demand for surgical masks following the recent health precautions due to coronavirus. Using a simple linear demand curve and alternatively examining the impacts of requirements that mandate (a) the wearing of masks by frontline workers; (b) suggested but not required masking by the whole public; and (c) compulsory masking by the whole public. The impacts of the different scenarios on the price elasticity of demand are determined along with the slope (or the rate of change) of elasticity. Some of these results differ when a non-linear demand curve is considered instead. The equilibrium mask prices increase when masks are universally mandated, whereas the consumer surplus is higher when masks are recommended but not mandated. However, the ranking of consumer surplus is shown to be sensitive to the supply elasticity of masks. These considerations enable a structured means to view the demand implications of masking requirements and provide some food for policy thought.
Keywords: 330; consumer surplus; coronavirus; COVID-19; demand analysis; demand complementarity; elasticity; health; market equilibrium; regulation